Micro-RNA signature of lymphovascular space involvement in type 1 endometrial cancer - Canlorbe, Geoffroy; Castela, Mathieu; Bendifallah, Sofiane; Wang, Zhe; Lefevre, Marine; Chabbert-Buffet, Nathalie; Aractingi, Selim; DaraÏ, Emile; Méhats, Céline; Ballester, Marcos (Histology and histopathology, 2017)
Lymphovascular space involvement (LVSI) is a major prognostic factor in type 1 endometrial cancer (EC). However, its use has been criticized because of poor subjectivity. MicroRNA signatures have recently been linked to EC pathologic characteristics. The aim of this study was to evaluate whether microRNA profiles of type 1 EC can be related to LVSI status and used as a tool to adapt therapy. MicroRNA expression was assessed by chip analysis and qRT-PCR in 12 formalin-fixed paraffin-embedded grade 2 EC specimens with positive LVSI and in 12 specimens with negative LVSI. Various statistical analyses, including enrichment analysis and a minimum p-value approach, were performed. The expression levels of microRNAs 34c-5p, -23b-5p, and 23c were significantly lower in the EC with positive LVSI compared to those with negative LVSI. Women with a microRNA-34c-5p fold change <0.15 were more likely to have positive LVSI status (92.3%) compared with those with a microRNA-34c-5p fold change >0.15 (0.0%), p<0.001. Furthermore, women with a microRNA-23b-5p fold change <0.51 were more likely to have positive LVSI status (90.0%) compared with those with a microRNA-23b-5p fold change >0.51 (21.4%), p=0.003. This was the first study to investigate the relative expression of microRNA in type 1 EC according to LVSI status. This microRNA expression profile may provide a basis for further study of the microRNA function in EC, and be used as a diagnostic tool for LVSI status.